90 A RETROSPECTIVE COHORT STUDY COMPARING THE CLINICAL CHARACTERISTICS, TREATMENT AND OUTCOMES OF BIOPSY-CONFIRMED SARCOIDOSIS IN LATE-ONSET AND YOUNGER-ONSET PATIENTS. (25th October 2022) - Brennan, M; Phelan, S; Breen, D
Abstract: Background: Late-Onset Sarcoidosis (LOS) accounts for up to one-third of cases and is diagnostically challenging due to the difficulty in satisfactorily excluding malignancy and infection, often necessitating repeated investigations. Endobronchial Ultrasound (EBUS) is the gold standard for diagnosing pulmonary sarcoidosis. This study aims to compare the clinical presentation, treatment and outcomes in patients with biopsy confirmed sarcoidosis in older and younger patients Methods: A retrospective cohort analysis was performed on all patients with EBUS-confirmed sarcoidosis at a tertiary referral centre between 2012 and 2019. Electronic healthcare records were reviewed to obtain information on clinical presentation, confirmatory investigations, treatment and outcomes. LOS was defined as patients aged >65 years Results: In total, 247 patients were included, 68.8% were male. LOS accounted for 9.3% (n=23).Extra-pulmonary and systemic features were less common in LOS (26.1% vs 58%, p<0.002). There was no difference in systemic treatment between cohorts (84.6% vs 67.9%, p=0.21) and LOS patients experienced comparably high rates of satisfactory outcomes. At follow up, the majority of patients either improved or achieved clinical stability in both groups (92.3% vs 76.1%, p=0.18). Clinical and/or radiological progression occurred in 7% in both groups with no reported deaths. Confirmatory investigations were infrequent and EBUS was safe and well-tolerated in older patients. Conclusion: LOS was lower than expected and extra-pulmonary involvement was uncommon suggesting a pre-selected population. Referral for EBUS should be considered as first line for older patients with unexplained thoracic adenopathy provided further diagnostic investigations are in line with their goals of care. Clinical outcomes were excellent with low rates of progression, extra-pulmonary organ involvement and systemic therapy initiation, differing from prior studies and may represent less severe disease at diagnosis, enhanced diagnostic certainty or referral bias.